A COMPARATIVE ANALYSIS, THROUGH GEOGRAPHICAL ACCESSIBILITY, OF URBAN PUBLIC TRANSPORT SYSTEMS IN CITIES OF COLOMBIA'S COFFEE-GROWING REGION - Jorge Alberto MONTOYA; Diego Alexander ESCOBAR; Carlos Alberto MONCADA (Geo Journal of Tourism and Geosites)
Valuing urban public transport plays a vital role in the growth and development of a city. In addition, an exemplary system connection allows the formation of functional relationships between the different users and the surrounding environment. That is why, in this research, it is proposed as an objective to carry out a comparative analysis of the levels of coverage offered by Public Transport Systems in cities of the Colombian coffee region to visualize the current state of operation of each city. The research methodology uses geographic accessibility as a visualization tool complemented with the analysis of sociodemographic coverage. The main result is that the assessment of accessibility and coverage shows that the population has easy access in a travel time of less than 35 minutes. It can also be concluded that the evaluation process provides a broad view of the levels of transport supply in each city.